Beyond Academics: The Impact of Universal Design for Learning on the Subjective Well-Being of Children with Special Needs - Reswita, Reswita; Wahyuni, Sri; Syahdan, Syahdan (Jurnal Pendidikan Progresif, 2025)
Beyond Academics: The Impact of Universal Design for Learning on the Subjective Well-Being of Children with Special Needs. Equity is another key area in which inclusive education of children with special needs is of interest, aiming to enhance their quality of life, including subjective well-being, a significant aspect of child development. Objectives: This research aims to investigate the impact of the Universal Design for Learning approach on the subjective well-being of children with special needs. The proposed research examines how the subjective well-being of children with special needs is affected by the Universal Design for Learning (UDL) strategy. Methods: This study employed a quasi-experimental design. The UDL strategy acts as the independent variable, while subjective well-being is the dependent variable. This study involved a total of 36 children with special needs, of whom 24 were selected using purposive sampling. They were divided into two groups: an experimental group and a control group, each comprising 12 participants. The data obtained were evaluated using non-parametric and descriptive statistical methods. Findings: The result showed a significant increase in subjective well-being for the children in the experimental group compared to the control group, with a p-value of 0.002 (p < 0.05). Finally, it has been discussed that the application of the Universal Design for Learning approach has a substantial influence on the way children perceive themselves. Conclusions: The application of the UDL approach significantly improves the subjective well-being of children with special needs, demonstrating the importance of integrating UDL into the inclusive education curriculum. These findings encourage the development of more adaptive education policies and psychosocial interventions that support children's social-emotional development. Keywords: children with special needs, educational approach, subjective well-being, treatment effect, universal design for learning